2022
DOI: 10.1371/journal.pone.0267987
|View full text |Cite|
|
Sign up to set email alerts
|

Toxic and repellent impacts of botanical oils against Callosobruchus maculatus (Bruchidae: Coleoptera) in stored cowpea [Vigna unguiculata (L.) Walp.]

Abstract: Cowpea (Vigna unguiculata) is an important legume which is consumed globally for protein intake, particularly in Asian states. It is a well-known source of dietary fiber, protein, minerals, and vitamins. The cowpea grains are stored after harvest and used till the next harvest. However, the grains are infested by storage pests, primarily Callosobruchus maculatus. Hence, effective management strategies are needed to protect the stored grains form the pests. This study assessed the efficacy of some edible oils i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…The study on the toxic and repellent effect of mustard, neem, poppy, and pumpkin at four different concentrations 0.5, 1.0, 1.5, and 2.0 mL per 100 g grain, signi cantly affected the mortality of C. maculatus after one day. Among those tested botanical oils, grain treated with neem oil resulted in highest mortality (Nisar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study on the toxic and repellent effect of mustard, neem, poppy, and pumpkin at four different concentrations 0.5, 1.0, 1.5, and 2.0 mL per 100 g grain, signi cantly affected the mortality of C. maculatus after one day. Among those tested botanical oils, grain treated with neem oil resulted in highest mortality (Nisar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This hole eventually led to seed damage and contributed to percentage weight loss. Similarly, Nisar et al (2022) reported that weight loss, damage percentage, and holes in the grains were not recorded because F 1 progeny did not emerge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our outcomes that neem and castor oils worked as a surface protectants are close to Rahman and Talukder (2006) they used different plants oil of neem, safflower and sesame to observe their surface protectants efficacy on black grams against C. maculatus and revealed that among different oils neem oil was the best surface protectant. Nisar et al (2022) also assessed the effectiveness of some botanical essential oils against C. maculatus i.e., Neem, mustard, pumpkin and popy. They prepared o.5, 1.0, 1.5 and 2.0 mL concentrations of the oils.…”
Section: Seeds Germination Testmentioning
confidence: 99%
“…The PLOS ONE Editors retract this article [ 1 ] because it was identified as one of a series of submissions for which we have concerns about authorship, competing interests, and peer review. We regret that the issues were not addressed prior to the article’s publication.…”
mentioning
confidence: 99%